La práctica del baloncesto como medio alternativo para ocupar el tiempo libre de la juventud del cantón Vinces, 2021 - Sevillano Campos, Melanny Nicoll (2021)
Basketball is a very popular sport and its practice is carried out by men and women, children and adults, even there are elderly people who still practice it, it is a sport of crowds that attracts young people and adolescents with great enthusiasm, who only require of a space and the necessary materials to be practiced and that can be used to be used in free time. The objective of this research work is to analyze the effect of basketball as an alternative to occupy the free time of young people from the Vinces canton, 2021, hoping to generate expectations that promote the implementation of programs for the massification of the same in the sector involved in the study For the development of this research work, the research methodology was used, in which it shows a qualitative and cross-sectional approach design, with a documentary and field modality, followed by the type of descriptive research, the methods that are inductive-deductive and analytical-synthetic, data collection techniques applied to a sample of 93 involved, distributed as follows: 3 parish authorities, 40 young people and 50 parents, obtaining as results that young people if they want to practice basketball in their free time, for which the following alternative proposal is suggested: design a program for the productive use of free time through the practice of basketball in the Vinces canton, the bibliography and the annexes.